Meningkatkan Daya Saing dan Efisiensi Operasional UMKM Melalui Teknologi dan Inovasi Digital - Rosyalia, Verra; Setyasari, Untung Eko; Kurniadi, Yudi (Lembaga Dongan Dosen, 2023)
This community service activity aims to provide knowledge and awareness to UMKM players about the importance of implementing digital technology and innovation in increasing competitiveness and operational efficiency. Through this training and mentoring, it is hoped that UMKM can provide better insight into the potential benefits of technology. This service activity is carried out through seminars with the delivery of material about the importance of transforming conventional marketing methods to digital, creating logos for UMKM who do not yet have a product logo. The result of this service activity is increasing the knowledge of UMKM players regarding the importance of using technology in the marketing process to make it easier to introduce products, product logos created for UMKM players who do not yet have a product logo